Evaluation of Natural Graminaceous Weed Flora in South Kerala for Fodder Purpose - Aneesa M S (Department of Agronomy, College of Agriculture, 1996)
An investigation was undertaken in the Southern districts of Kerala for the indentification and evalution of promising natural graminaceous weed specious for fodder purpose. The experiment was conducted in two steps. In the first part, a survey was conducted to identify the prominent grass weeds of Thiruvananthapuram, Kollam and Pathanamthitta districts. In the three districts surveyed, perennial grasses predominated among the weed specious. The prominent grass specious identified were Panicum Javanicum, Axonopus compressus, Cyrtococcum trigonum, Brachiaria ramose, Panicum repens, Cynodon dactylon, Dactyloctenium aegyptium, Eleusine indica, Echinochloa colonum, Chloris barbata, Rhynchelytrum repens, Sporobolus indicus and Eragrosstis tenella. Qualitative and quantitative comparison of the selected 15 grass specious with guines grass cv. Hamil constituted the second part of the study. This was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani in micro plots of 1 m 2 area and was laid out in Randomised Block Design with three replications. Guinea grass was found to be superior to the indigenous specious in terms of growth characters and green and dry fodder yields. Among the indigenous specious, highest green fodder yield was recorded by Panicum Javanicum and dry fodder yield by Rhynchelytrum repens. The protein content of grass specious varied from 5.84 to 15.00 per cent and Dactyloctenium aegyptium recorded the highest protein content. Guinea grass gave the highest protein yield owing to high dry matter production. Variation in crude fibre, ash, nitrogen, phosphorus, potassium, calcium, magnesium, copper, zinc and managanese contents was also observed among grasses. In the case of K : (Ca + Mg) ratio, all the 15 grass specious recorded higher values than the reported critical value of 2.2. Ca : P ratio was within the safe limits. In all the specious studied, the anti –nutritional factors like tannin and oxalate were well below the toxicity levels. Content of HCN and heavy metals could not be detected in any of the specious tried. Nutrient uptake also showed variation and guinea grass recorded the maximum. The quality index developed on the basis of nutritional and anti-nutritional factors of different grasses revealed that out of 15 indigenous grass specious tried, five were found superior to guinea grass in quality. Brachiaria ramose and Eleusine indica were observed to be the best.